Subalternity, Class-Consciousness and Resistance - Dirk Michel-Schertges (Social Work and Society)
The history of mankind is a history of survival, subjugation of external and internal nature as well as exploitation and mastery of humans. The exploitation of human labour by means of physical violence is a phenomenon that has been going on since prehistoric times, through the epochs of the Egyptians, Hellenes, Romans, European feudalism and colonialism up to modern times and the modern era of globalism. Starting from hierarchically ordered violent relationships in (small) groups, processes of planned and instrumentalized subjugation are aiming to master others and thus to"improve" the living conditions of the one's in power. This involves the violent expropriation and appropriation of social space and natural resources especially that of living labour. The focus of this text is on relations of oppression and consciousness that are reflected in the discussions of the "subaltern." That is, the constitution of (postcolonial) power relations and their relevance in order to understand contemporary social relations of domination and mastery in the light of subaltern consciousness.